Construção de uma tecnologia educativa para o cuidado do idoso acamado - Melo, Tereza Cristina Linhares Costa (2025)
The rapid aging of the population in recent decades has created an urgent need for effective and accessible solutions to meet the growing demand for specialized care. In this context, the proposed study becomes essential to ensure the well-being of bedridden elderly individuals and to provide training for caregivers, whether they are family members or professionals. The primary objective of the study was to develop and validate an educational video focused on home care for bedridden elderly individuals. The methodology was divided into two parts: initially, a scoping literature review was conducted to gather relevant bibliographic information. Subsequently, the educational technology in video format was constructed and validated, serving as a scientific basis for knowledge dissemination to the public.The research involved five expert judges, all healthcare professionals, including a geriatrician, a family physician, a speech therapist, a physiotherapist, and a nurse. To validate the video, a content and appearance validation instrument was created, comprising an adapted questionnaire with eight items. The Content Validity Index (CVI) was employed to assess the proportion of agreement among judges regarding various aspects of the instrument and its items, allowing for both individual item analysis and overall content evaluation. The study's results indicate that the produced material is of excellent quality and highly suitable for the target audience. The unanimous evaluations, coupled with a CVI of 1.0 across all items, underscore the video's effectiveness as an educational resource, making it a reliable tool for caregiver training and guidance. The combination of the experts' high qualifications and the positive assessment of all analyzed criteria ensures that the video fulfills its educational and formative role exceptionally well. In conclusion, the video stands out as a highly effective educational tool, combining clear communication with practicality, thereby facilitating the learning and application of best practices in the care of bedridden elderly individuals. By providing direct and objective guidance, the video significantly contributes to improving the quality of care, promoting more humanized and appropriate assistance tailored to the specific needs of this population.